Análise da transição florestal na Amazônia Legal - Morales, Lucas (Universidade Federal de São Carlos, 2023)
The Amazon Rainforest is of crucial importance for global environmental balance and the Brazilian economy, but it is in a state of progressive deforestation that affects its influence. Deforestation is caused by several factors including economic growth, agricultural expansion, livestock expansion, timber extraction, and investment in infrastructure. The implementation of the political-administrative region together with the Action Plan for the Prevention and Control of Deforestation in Legal Amazon (PPCDam) have had significant impacts on reducing deforestation rates. However, net increments in forest cover are not consistently observed in the region and occur mostly through the expansion of secondary forests at the expense of primary forests. Secondary forests have lower biodiversity and can cause significant losses in the complexity of the local ecosystem, harming species of fauna and flora. The forest transition theory seeks to analyze the long-term phenomenon in which the decline in forest area is replaced by forest regeneration, resulting in a TTF curve with a U-shaped pattern. These changes in forest cover are related to the optimal allocation of land use by agents, which can be affected by policies, market failures, and external factors. Thus, panel data model was used to identify the main determining factors in the changes in the proportion of forest area for the municipalities in the Legal Amazon from 2005 to 2020. Different demographic, economic, and environmental policy indicators were examined. The research results indicate that per capita GDP indicators contribute in the long term to an increase in forest proportion, while population density, agricultural GDP proportion, and average fine value are negatively related to forest areas. Therefore, the possibility of a U-shaped curve as indicated by the forest transition theory was observed.
Analysis of the forest transition in the Legal Amazon
Keywords: Amazônia; Amazônia legal; Teoria da Transição Florestal; Desmatamento; Amazon; Legal Amazon; Forest Transition Theory; Deforestation; CIENCIAS SOCIAIS APLICADAS::ECONOMIA